SOCIAL STATUS AND STANDARD OF LIVING OF THE RURAL POPULATION AS PREREQUISITES TO CHANGE THE SOCIAL PARADIGM OF THE DEVELOPMENT OF RURAL TERRITORIES IN RUSSIA - Ekaterina Vladimirovna KUDRYASHOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study In preparing the article, data from the Federal State Statistics Service of the Russian Federation, materials collected as a result of a survey of residents of rural areas, scientific works of Russian and foreign scientists were used. The study was based on the works of T. Kuhn and the theory of structural functionalism of T. Parsons and R. Merton. To determine the social status and standard of living of the population of rural areas, a questionnaire survey was conducted, during which the following were determined: the level of education, pension and social security, the amount of income from labor activity, wages of residents, as well as infrastructure provision of villages. The results of such a study showed that the current socio-economic situation in the countryside is characterized by a high level of unemployment, poverty, and negative trends in the social sphere.